2019
DOI: 10.3389/fmicb.2019.00869
|View full text |Cite
|
Sign up to set email alerts
|

Anti-pseudomonad Activity of Manuka Honey and Antibiotics in a Specialized ex vivo Model Simulating Cystic Fibrosis Lung Infection

Abstract: Pseudomonas aeruginosa causes problematic chronic lung infections in those suffering from cystic fibrosis. This is due to its antimicrobial resistance mechanisms and its ability to form robust biofilm communities with increased antimicrobial tolerances. Using novel antimicrobials or repurposing current ones is required in order to overcome these problems. Manuka honey is a natural antimicrobial agent that has been used for many decades in the treatment of chronic surface wounds with great success, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
5
13
0
Order By: Relevance
“…Our data corroborate the measurable antimicrobial activity of Manuka honey against a spectrum of clinical isolates from skin and soft tissue sources, including those with multi-drug resistance such as MRSA, ESBL producers, CRE, and MDR P . aeruginosa [6, 2730]. Lower MIC values were achieved against Staphylococcus species than with gram-negative pathogens, consistent with the overall trends of prior studies [3].…”
Section: Discussionsupporting
confidence: 77%
“…Our data corroborate the measurable antimicrobial activity of Manuka honey against a spectrum of clinical isolates from skin and soft tissue sources, including those with multi-drug resistance such as MRSA, ESBL producers, CRE, and MDR P . aeruginosa [6, 2730]. Lower MIC values were achieved against Staphylococcus species than with gram-negative pathogens, consistent with the overall trends of prior studies [3].…”
Section: Discussionsupporting
confidence: 77%
“…The decrease in S. aureus , A. baumanii , E. coli , S. Enteriditis and P. aeruginosa biofilm formation observed for Heather honey is reported here for the first time. Manuka honey decreased biofilm formation in P. aeruginosa , E. faecalis , A. baumanii , and E. coli , in agreement with previous studies [ 45 , 46 , 47 , 48 , 49 ]. Its effect on K. pneumoniae and S. Enteriditis biofilms has not been previously reported.…”
Section: Discussionsupporting
confidence: 92%
“…This prompted us to test its activity against a range of Gram-positive and Gram-negative single-species biofilms. This was done using a crystal violet assay, a commonly-used indirect method of biofilm quantification [ 50 ], and in comparison with Manuka honey, already known for its ability to decrease bacterial biofilm formation [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The decrease in S. aureus , A. baumanii , E. coli , S. Enteriditis and P. aeruginosa biofilm formation observed for Heather honey is reported here for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of sub-lethal exposure to manuka honey has received relatively little research attention although stepwise training experiments using planktonic cultures of Escherichia coli, P. aeruginosa, S. aureus and S. epidermidis suggest only transient reductions in sensitivity to honey ( Blair et al, 2009 ; Cooper et al, 2010 ). The anti-biofilm potential of manuka honey has been described ( Maddocks et al, 2012 ; Lu et al, 2019 ; Roberts et al, 2019 ), although elevations in imipenem MIC of up to 4-fold and increased biofilm forming potential have been observed in cultures derived from honey exposed sessile communities ( Camplin and Maddocks, 2014 ). Passaging experiments using other antimicrobials have demonstrated that adaptation can manifest in ways other than through changes in drug sensitivity ( Latimer et al, 2012 ; Lu et al, 2014 ; Henly et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%